1990
DOI: 10.1093/jac/26.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane proteins responsible for the penetration of β-lactams and quinolones in Pseudomonas aeruginosa

Abstract: Porin-deficient mutants of Pseudomonas aeruginosa PAO1 were selected by isolating latamoxef-resistant mutants following chemical mutagenesis. Highly latamoxef-resistant mutants had alterations in both the outer membrane proteins and penicillin-binding protein 3, a lethal target of latamoxef. Both of these alterations may be essential for cells to acquire high resistance to latamoxef. Many of the latamoxef-resistant mutants were also resistant to new quinolones and chloramphenicol. Resistance to these compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…aeruginosa also produces protein E2 (formerly protein E). The level of this protein was found to be decreased in a mutant showing a wide range of increased resistance to cephalosporins and fluoroquinolones (752). Otherwise, its properties are not known (244).…”
Section: Specific Channelsmentioning
confidence: 98%
See 1 more Smart Citation
“…aeruginosa also produces protein E2 (formerly protein E). The level of this protein was found to be decreased in a mutant showing a wide range of increased resistance to cephalosporins and fluoroquinolones (752). Otherwise, its properties are not known (244).…”
Section: Specific Channelsmentioning
confidence: 98%
“…OprE (earlier named protein E1) was found to be decreased in some P. aeruginosa mutants resistant to cephalosporins carrying double negative charges (752) and was thus thought to be a specific channel. It was then cloned and sequenced (751).…”
Section: Specific Channelsmentioning
confidence: 99%
“…Presently, data suggesting that OprF is a porin that leads to antibiotic resistance (35,38,45) and also that OprF is not a porin and is not responsible for antibiotic resistance exist (4,47). We plan to test our hypothesis regarding the structural role of OprF as well as its role in fluoroquinolone uptake and antibiotic resistance by inserting an expression vector containing the cloned OprF gene into our laboratory-derived fluoroquinolone-resistant isolates and testing for function.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic characterization by DNA sequencing of gyrA from E. coli reveals that mutations leading to fluoroquinolone resistance are clustered within a narrow region between nucleotides 199 (Ala-67) and 318 (Gln-106) (21). It has been suggested that mutants possessing a single nucleotide change (point mutation) produce single changes in amino acid sequence which result in an altered DNA gyrase which either reduces the affinity of the fluoroquinolone for the enzyme or blocks the access of the antibiotic to the DNA-DNA gyrase complex (21,39).In addition to DNA gyrase changes, fluoroquinolone resistance in P. aeruginosa can occur as a result of alterations in the outer membrane (2,3,12,14,20,27,31,38,45,46). Resistance selection with fluoroquinolones results in many instances in changes in outer membrane proteins and is manifested as not only resistance to fluoroquinolones but multiple antibiotic resistance (Mar) including beta-lactams, tetracyclines, and chloramphenicol (2,3,12,27,37,38).…”
mentioning
confidence: 99%
See 1 more Smart Citation